2021
DOI: 10.1039/d1cy01758f
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting the CO2 hydrogenation pathway via the synergic effects of iron carbides and iron oxides

Abstract: Owing to the chemical inertness and thermodynamic stability of CO2, efficiently regulate the products selectivity in CO2 hydrogenation is still a big challenge. Without impairing the CO2 reactivity and stability,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…In contrast, the transformation of the CO 2 /H 2 feed over magnetite (Fe 3 O 4 ) into gaseous CO, CH 4 and hydrocarbons could be so rapid, that possible intermediates are not observable by DRIFTS at the applied conditions. In that regard again also other factors such as the partial pressures might have an important influence on the ability to observe such adsorbates [51] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the transformation of the CO 2 /H 2 feed over magnetite (Fe 3 O 4 ) into gaseous CO, CH 4 and hydrocarbons could be so rapid, that possible intermediates are not observable by DRIFTS at the applied conditions. In that regard again also other factors such as the partial pressures might have an important influence on the ability to observe such adsorbates [51] …”
Section: Resultsmentioning
confidence: 99%
“…In that regard again also other factors such as the partial pressures might have an important influence on the ability to observe such adsorbates. [51]…”
Section: Chemcatchemmentioning
confidence: 99%
“…[8][9][10] The reaction scheme not only achieves the large-scale storage of hydrogen manufactured during the water electrolysis, but also reduces CO 2 emissions along with efficient utilization. 11,12 The hydrogenation of CO 2 to olefins has attracted widespread interest. 13,14 Light olefins are gateway molecules in the chemical industry, while heavy olefins are key raw materials in the production of polymers, alcohols, lubricants and detergents.…”
Section: Introductionmentioning
confidence: 99%
“…8–10 The reaction scheme not only achieves the large-scale storage of hydrogen manufactured during the water electrolysis, but also reduces CO 2 emissions along with efficient utilization. 11,12…”
Section: Introductionmentioning
confidence: 99%
“…In general, light olefins can be produced from CO 2 hydrogenation via three main paths: direct CO 2 conversion, , the CO intermediate route involving the reverse water–gas shift (RWGS) reaction combined with the Fischer–Tropsch (FT) process, and the methanol intermediate route. To date, Fe-based catalysts have been most widely explored in the hydrogenation of CO 2 to produce light olefins via the above CO 2 –FT route, , where the CO intermediate is usually generated on the Fe 3 O 4 component, and a subsequent FT process occurs on iron carbides. In addition, some 3d transition metals (Cu, Ni, Co) or alkali metals (K and Na) as promoters or electron donors are incorporated into catalysts to inhibit the secondary hydrogenation of olefins, thus promoting the production of C 2+ products. For the CO 2 –FT route, Hagg carbide (χ-Fe 5 C 2 ), which is considered the most recognized catalytically active phase, can benefit the production of long-chain hydrocarbons. ,, Furthermore, the synergic effect between Fe 3 O 4 and iron carbide facilitates the formation of alkenes and alcohols in CO 2 hydrogenation . Recently, it has been reported that the Fe 3 O 4 component can substantially impact the hydrogenation of CO 2 toward the production of hydrocarbons rather than iron carbides .…”
Section: Introductionmentioning
confidence: 99%